KUALITAS PELAYANAN CUSTOMER SERVICE, PROMOSI TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN PADA GAME ONLINE VALORANT - Irfan Arif Husen (Bajang Institute, 2023)
This study aims to determine the Quality of Customer Service, Promotion of Repurchase Interest through Customer Satisfaction in the Valorant Online Game. Customer Service, Promotion, Consumer Satisfaction as the dependent variable, Meanwhile, repurchase interest as an Intervening variable, Meanwhile, consumer satisfaction as an independent variable. The strategy in this research is associative research with a quantitative approach. Data collection in this study was carried out by distributing research instruments in the form of questionnaires to 100 Valorant game players which were measured using a Likert scale. The analysis in this study uses Smart PLS Ver 4 software. The statistical analysis tool uses the Partial Coefficient of Determination, the Coefficient of Determination. The results of the study show that partially Customer Service has a significant effect on Consumer Satisfaction, Promotion has a significant effect on Consumer Satisfaction, Customer Service has no significant effect on Repurchase intention, Promotion has no significant effect on Repurchase intention, Customer satisfaction has a significant effect on Repurchase intention